Identification and Characterization of Assembly Proteins of CS5 Pili from Enterotoxigenic Escherichia coli - Duthy, Thomas G. (American Society for Microbiology, 2002)
This study investigated the role of three genes comprising part of the operon which encodes CS5 pili from enterotoxigenic Escherichia coli. In-frame gene deletions were constructed, and the effects on biogenesis of the pili were examined. A deletion in csfB abolished CsfA major subunit accumulation in the periplasm, which could be restored by trans-complementation with a complete copy of the csfB gene. Localization studies using an antibody against CsfB showed that this protein was periplasmically located, and thus CsfB is likely to function as the specific chaperone for CsfA. An in-frame deletion mutation in the csfE gene resulted in pili approximately three times longer than those of the wild-type strain, thereby indicating a role for CsfE in pilus length regulation. Localization studies using an antibody generated against CsfE showed low-level CsfE accumulation in the outer membranes. Modulation of csfE expression in trans did not reduce the mean length of the pilus below that of the wild type, which indicated that CsfE is not rate-limiting for termination of pilus assembly. Interestingly, a deletion in the csfF gene also resulted in an elongated pilus morphology identical to that of the csfE deletion strain. However, unlike CsfE, CsfF was shown to be rate-limiting for termination of assembly, since overexpression of CsfF in a csfF deletion strain resulted in a significant decrease in the mean length of the pilus compared to that of the wild type. When the same construct was introduced into the wild-type strain, pilus expression was abolished. Since CsfF bears significant homology to the proposed CsfB chaperone, CsfF was predicted to act as the specific chaperone for CsfE. A double deletion in the csfB and csfF genes was shown to abolish the periplasmic accumulation of both CsfA and CsfD pilins, which could be restored individually only when the strain was trans-complemented with a wild-type copy of csfB or csfF, respectively. Therefore, CsfF may chaperone not only CsfE but also CsfD. A model for CS5 biogenesis is also proposed based on these and previous observations.